Charlotte's web - White, E. B. (Elwyn Brooks); Williams, Garth (New York : Scholastic, 1952)
Wilbur, the pig, is desolate when he discovers that he is destined to be the farmer's Christmas dinner until his spider friend, Charlotte, decides to help him.
Keywords: Children's stories; Fantasy fiction